Innovation and adaptation of training needs to business demand - Ferrer-Sapena, Antonia; Aleixandre-Benavent, Rafael (Anuario ThinkEPI, 2011)
The results of the 2010 Cotec report on the culture of innovation among Spanish young people on the European scene are not very optimistic. There is a socioeconomic and cultural environment that is not ideal to promote an innovation culture. Therefore, analyzing the situation and taking the results into account can help to improve the skills of young people. The interactions between academia and industry and the factors affecting employability are discussed. Also crucial to increase innovation is to have a stable job market. Success stories of European institutions in which there is a direct relationship between companies and universities are described.